Profiles in conspiracism: Associations with two psychiatric syndromes, religiosity and pandemic-related health behaviors - Minzenberg, Michael J.; Yoon, Jong H. (Frontiers in Psychiatry, 2022)
Introduction. Conspiratorial beliefs are often maladaptive for individuals and dangerous for societies. Other prevalent belief systems such as (normative) religious belief and (pathological) delusional belief show parallels to conspiratorial beliefs, which may also be linked to excessive social media exposure. We conducted an online survey to characterize heterogeneous profiles of conspiracy-mindedness, with respect to these other phenomena. Methods. 836 American adults from online panels completed validated questionnaires including the Conspiracy Mindedness Questionnaire (CMQ), Centrality of Religion Scale (CRS), Peters Delusion Inventory (PDI; 21-item version), and Facebook Addiction Scale (FAS). Additionally, they completed 4 questions addressing categorical belief in the origin of SARS-Cov-2, and pandemic-related health behaviors. Total scores on each questionnaire were Z-transformed and entered into K-means cluster analysis. Cluster membership was used in post-hoc analyses to compare pandemic-related items. Results. An optimal included 3 clusters with above-mean (high) CMQ and 3 below-mean (low) CMQ scores. The 3 high-CMQ clusters included: 1) high-religion, low-social media addiction; 2) high religion, social media addiction and delusion; 3) low religion and delusion. High-CMQ clusters 1 and 2 each had rates of zoonotic and malevolent viral origin beliefs that were relatively lower and higher than the grand sample rates, respectively. Significant differences in intended pandemic health-related behaviors among the high-CMQ clusters (compared to the rest of the sample) included Cluster 1 - high on Precautions and low on Vaccination; Cluster 2 - high on Precautions and Testing; Cluster 3 - high on Precautions. Respondents who endorsed SARS-Cov-2 origin beliefs (across clusters) that were least plausible and most malevolent were least inclined to engage in pandemic health behaviors. Conclusions. Distinct subpopulations of persons with high conspiracy-mindedness exist, which are highly heterogeneous in their other coexisting beliefs and behaviors. Some of these are pathological, such as delusional belief and social media addiction-like behavior, and they have varied associations with pandemic-related belief and behavior. These results, while cross-sectional, suggest that the psychological origins and consequences of conspiratorial beliefs may not be unitary. Instead, conspiratorial belief may be a common expression of diverse psychological and social/experiential factors, and in turn exert varied influence on decisions and overt behavior.